The demographic characteristics, practice experiences, roles and development needs of family physicians who graduated between 2008-2018 from the Family Medicine Blended Learning 2 Year Diploma run by the Christian Medical College, Vellore, India - Marcus, Tessa S. (University of Pretoria, 2024)
Thesis (PhD (Family Medicine))--University of Pretoria, 2023.